Studi Komparasi Karakteristik Mekanik Serat Alam sebagai Bahan Anti Peluru: Jurnal Review - Haziza, Ellsa Putri; Aritonang, Sovian; ., Imastuti (Fakultas Teknik UMSU, 2024)
Indonesia has abundant natural resources, but if they are not optimized, they will end up as waste. Natural fibers come from plants, animals or minerals, standing out with certain advantages that differentiate them from artificial fibers. These advantages include the ability to decompose naturally (biodegradable), good strength and durability, and sustainable income through farming or capturing natural resources that produce fiber. The impact strength of composite materials combining natural fibers and synthetic fibers in ballistic material applications has grown rapidly. However, the use of synthetic fibers as reinforcement in composite materials has had a negative impact on the environment because they are difficult to decompose naturally and can cause long-term environmental disturbances. Therefore, utilizing natural fibers as reinforcement in composite materials is considered a good step. This update in research compares the characteristics of natural fibers in the use of ballistic materials. The natural fibers used are palm fiber, snake fruit midrib fiber, corn husk fiber, pineapple leaf fiber, water hyacinth fiber, hemp fiber. Ballistic material made from natural fibers